Evaluating the efficacy of Chenopodium murale plant extract in inhibiting Streptococcus mutans and reducing dental caries risk - Sumaira Kanwal; Shazia Perveen; Huma Hameed; Sadia Tahir; Rehmana Rashid; Mohammad Raish; Sadia Bashir; Khudija Zaffar; Ali Irfan; Katarzyna Kotwica-Mojzych; Saleha Faheem; Ajaz Ahmad; et al. (Scientific Reports)
Abstract The relationship between Streptococcus mutans and dental caries has been a key focus of research due to the widespread prevalence of caries in humans. In this study, we have investigated the antimicrobial activity of Chenopodium murale (C. murale) extract against Streptococcus mutans by the application of 10 µL of ethanolic extract. The minimum bactericidal concentration test was used for antimicrobial sensitivity by the application of ethanolic extracts of C. murale. The zone of inhibition diameter made by the extract of C. murale, was measured at 12 mm and compared with the standard reference ampicillin and clindamycin antibiotic drugs, measured at 20 mm and 30 mm, respectively. Moreover, the FTIR analysis showed alkyl halide, phenyl, carbonyl, alkane, amines, and alcohol functional groups in C. murale extract. The C. murale plant extract has significant and comparable therapeutic efficacy with reference to the ampicillin reference drug against the bacterial strain Streptococcus mutans, on account of scavenging bond stretches with fewer side effects owing to its natural origin. Further, presence of coumarin in the pure extract of C. murale was confirmed by TLC method. The anti-Streptococcus mutans activity of the C. murale ethanolic extract was found with the MIC of 1.469 mg/mL and MBC of 4.260 and cariogenic properties of Streptococcus mutans linked to pH drop was also inhibited significantly. Our study clearly indicated that this plant extract thus can potentially be used as a commercialized product in near future for the prevention of dental caries.